Diffusion-defining atomic-scale spinodal decomposition within nanoprecipitates. Issue 12 (December 2018) - Orthacker, Angelina; Haberfehlner, Georg; Taendl, Johannes; Poletti, Maria; Sonderegger, Bernhard; Kothleitner, Gerald
Abstract Stoichiometric precipitates owe their fixed composition to an ordered crystal structure. Deviations from that nominal value, however, are encountered at times. Here we investigate composition, structure and diffusion phenomena of ordered precipitates that form during heat treatment in an industrially cast Al–Mg–Sc–Zr alloy system. Experimental investigations based on aberration-corrected scanning transmission electron microscopy and analytical tomography reveal the temporal evolution of precipitate ordering and formation of non-equilibrium structures with unprecedented spatial resolution, supported by thermodynamic calculations and diffusion simulations. This detailed view reveals atomic-scale spinodal decomposition to majorly define the ongoing diffusion process. It is illustrated that even small deviations in composition and ordering can have a considerable impact on a system's evolution, due to the interplay of Gibbs energies, atomic jump activation energies and phase ordering, which may play an important role for multicomponent alloys. Atomic-scale spinodal decomposition enabled diffusion was observed within ordered nanoprecipitates that have structural imperfections, resulting from dynamic interaction of Gibbs energy, activation energy of atomic jumps and phase ordering in multicomponent alloys.